1986
DOI: 10.1177/106002808602001208
|View full text |Cite
|
Sign up to set email alerts
|

Dialyzability and Pharmacokinetics of Indomethacin in Adult Patients with End-Stage Renal Disease

Abstract: Indomethacin, a nonsteroidal antiinflammatory drug, has been shown to be effective for the treatment of pericarditis in chronic hemodialysis patients. Data regarding the dialyzability of indomethacin in these patients, however, is lacking. The aim of this study, therefore, was to evaluate (1) the dialyzability, and (2) the absorption and elimination kinetics of indomethacin, using six stable anephric adult patients who were maintained on chronic hemodialysis and were receiving indomethacin for the management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Studies of other acetic acid derivatives, etodolac, bromfenac and indomethacin, in CKD and ESRD patients, do not suggest that any dose adjustment is necessary .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of other acetic acid derivatives, etodolac, bromfenac and indomethacin, in CKD and ESRD patients, do not suggest that any dose adjustment is necessary .…”
Section: Methodsmentioning
confidence: 99%
“…These studies suggest that in ESRD, a higher dose of sulindac may be required for analgesic effect. Studies of other acetic acid derivatives, etodolac, bromfenac and indomethacin, in CKD and ESRD patients, do not suggest that any dose adjustment is necessary (167)(168)(169). Propionic acid derivatives (the -profens): 11 studies identified CKD Studies evaluating ketoprofen, ximoprofen and benoxaprofen have shown increased half-life in CKD (170)(171)(172)(173).…”
Section: Dialysismentioning
confidence: 99%